Application of Integrated Logistics Networks in Improving the Efficiency of Distribution and Delivery of Goods in Indonesia a Literature Review - Loso Judijanto; Nunut Asniar; Kushariyadi Kushariyadi; Eva Yuniarti Utami; Eliagus Telaumbanua (Sciences du Nord Economics and Business, 2024)
This research delves into the implementation of integrated logistics networks in Indonesia, a nation marked by its archipelagic geography and diverse logistical challenges. Through a systematic literature review, empirical case studies, and rigorous research methods, the study unravels the intricate dynamics of challenges, strategies, benefits, and drawbacks associated with integrating logistics networks. The identified challenges encompass infrastructural inadequacies, regulatory complexities, and technological barriers, while strategies focus on public-private partnerships, technological integration, and workforce capacity building. The potential benefits of integrated networks, including cost reduction and improved customer satisfaction, are balanced against drawbacks such as initial implementation costs and technological risks. Real-world case studies provide tangible examples of successful and unsuccessful implementations, offering practical insights for stakeholders. The synthesis of findings underscores the interconnected nature of these elements and provides recommendations for policymakers, industry practitioners, and avenues for future research. This research contributes to a nuanced understanding of the logistics landscape in Indonesia, guiding stakeholders in navigating challenges and optimizing the efficiency of distribution and delivery networks.